Machine learning to aid in the diagnosis of acute heart failure in the emergency department. (14th October 2021) - Doudesis, D; Lee, K K; Anwar, M; Astengo, F; Newby, D; Japp, A; Tsanas, A; Shah, A; Richards, M; McMurray, J; Mueller, C; Januzzi, J; et al.
Abstract: Background: B-type natriuretic peptide (BNP) and mid-regional pro-atrial natriuretic peptide (MRproANP) testing are recommended to aid in the diagnosis of acute heart failure. However, the application of these biomarkers for optimal diagnostic performance is uncertain. Methods: We performed a systematic review and harmonised individual patient-level data to evaluate the diagnostic performance of BNP and MRproANP for the diagnosis of acute heart failure using random-effects meta-analysis. We subsequently developed and externally validated a decision-support tool called CoDE-HF for both BNP and MRproANP that combines the natriuretic peptide concentrations with clinical variables using machine learning to report the probability of acute heart failure for an individual patient. Results: Fourteen studies from 12 countries provided individual patient-level data in 8, 493 patients for BNP and 3, 847 patients for MRproANP, in whom, 48.3% (4, 105/8, 493) and 41.3% (1, 611/3899) had an adjudicated diagnosis of acute heart failure, respectively. The negative and positive predictive values of guideline-recommended thresholds for BNP (100 pg/mL) and MR-proANP (120 pg/mL) were 93.6% (95% confidence interval 88.4–96.6%) and 68.8% (62.9–74.2%), and 95.6% (92.2–97.6%) and 64.8% (56.3–72.5%), respectively. However, we observed significant heterogeneity in the diagnostic performance across important patient subgroups (Figure 1). In the external validation cohort, CoDE-HF was well calibrated with excellent discrimination in those without prior acute heart failure for both BNP and MRproANP (area under the curve of 0.946 [0.933–0.958] and 0.943 [0.921–0.964], and Brier scores of 0.105 and 0.073, respectively). CoDE-HF performed consistently across all subgroups for both BNP and MRproANP, and identified 30% and 65.7% at low-probability (negative predictive value of 99.1% [98.8–99.3%] and 99.1% [98.8–99.4%]), and 30% and 17.3% at high-probability (positive predictive value of 91.3% [90.7–91.9%] and 70.0% [68.5–71.4%]) in those without prior heart failure, respectively (Figure 2). Conclusion: In an international collaborative analysis, we observed that guideline-recommended thresholds for BNP and MRproANP to diagnose acute heart failure varied significantly across patient subgroups. A decision-support tool using machine learning to combine natriuretic peptides as a continuous measure and other clinical variables provides a more accurate and individualised approach. Funding Acknowledgement: Type of funding sources: Other. Main funding source(s): Medical Research Council and British Heart Foundation